Designing User Experience and User Interface of a B2B Textile e-Commerce using Five Planes Framework - Alvi Syahrina; Tien Fabrianti Kusumasari (School of Industrial and System Engineering, Telkom University, 2020)
The textile industry needs an e-commerce platform to facilitate purchase of textile goods and to improve connectivity between industries. The textile industry has distinct characteristics from other industry, from its supply chain characteristics to the details of goods sold. Therefore, Indonesia Smart Textile Industry Hub (ISTIH) as a textile e-commerce platform needs to implement different strategy from e-commerce in general. Different strategies will affect the design of user experience or user experience in e-commerce. This journal will discuss how to design e-commerce specifically for textiles using the five planes method. The strategy plane produced the objectives and user needs of e-commerce, the scope plane produced the list of the required features, the structure plane produced detailed flow of user activities, the skeleton plane produced layout designs and information organization in the form of wireframes, and the surface plane produced the design up to the level of interface detail. The interface detail is also designed to meet eight golden rules of interface design. The output produced in this study is the design of the textile e-commerce interface on the alpha version of the website.